2018
DOI: 10.4067/s0718-58392018000200165
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen application at the booting stage affects 2-acetyl-1-pyrroline, proline, and total nitrogen contents in aromatic rice

Abstract: Aromatic rice (Oryza sativa L. subsp. japonica Kato) is globally popular due to its pleasant aroma and enchanting flavor. 2-Acetyl-1-pyrroline (2-AP) is recognized as the only major flavoring compound in aromatic rice. Plant nutrition affects the production and accumulation of 2-AP in rice, but the effect of time-specific nutrient application during the developmental phases of rice on 2-AP has not yet been reported. Three N levels (N0: 0 kg ha -1 , N1: 30 kg ha -1 , and N2: 60 kg ha -1 ) at the booting stage w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 27 publications
(47 reference statements)
1
25
0
Order By: Relevance
“…The effect of the environmental factors such as the temperature, light and nutrition, and the cultivation practices such as irrigation, fertilization, and plant regulators on 2AP formation during rice growth period have been evaluated in previous studies (Bhattacharjee et al, 2002; Champagne, 2008; Goufo et al, 2010; Poonlaphdecha et al, 2012; Yang et al, 2012; Mo et al, 2015, 2016; Li et al, 2016, b). Those results suggested that it is feasible to regulate the 2AP content in fragrant rice with moderate irrigation and nitrogen application (Yoshihashi et al, 2002; Itani et al, 2004; Tian et al, 2010; Wang et al, 2013; Bao et al, 2018; Mo et al, 2018). It have been reported that water and nitrogen management at tillering stage can regulate 2AP accumulation (Li, Tang, et al, 2014; Ren et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of the environmental factors such as the temperature, light and nutrition, and the cultivation practices such as irrigation, fertilization, and plant regulators on 2AP formation during rice growth period have been evaluated in previous studies (Bhattacharjee et al, 2002; Champagne, 2008; Goufo et al, 2010; Poonlaphdecha et al, 2012; Yang et al, 2012; Mo et al, 2015, 2016; Li et al, 2016, b). Those results suggested that it is feasible to regulate the 2AP content in fragrant rice with moderate irrigation and nitrogen application (Yoshihashi et al, 2002; Itani et al, 2004; Tian et al, 2010; Wang et al, 2013; Bao et al, 2018; Mo et al, 2018). It have been reported that water and nitrogen management at tillering stage can regulate 2AP accumulation (Li, Tang, et al, 2014; Ren et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the genetic factor is recognized to play the important role in affecting the aroma biosynthesis in fragrant rice (Lorieux et al, 1996; Bradbury et al, 2008; Fitzgerald et al, 2008), however, many environmental factors and management practices have been reported to affect the 2AP biosynthesis in fragrant rice (Bhattacharjee et al 2002; Champagne, 2008; Gay et al, 2010; Yang et al 2012; Mo et al, 2016, b). For instance, light intensity, temperature, soil nutrient, salinity as well plant nutrition such as silicon, Mn, and Zn application are external plant factors that substantially affect the 2AP contents in fragrant rice (Fitzgerald et al, 2010; Poonlaphdecha et al 2012; Yang et al 2014; Li et al, 2016, b; Mo et al 2015, 2016,b, 2017, 2018, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that salt and shading treatment increased the 2AP and GABA contents in grain (Mo et al, ; Poonlaphdecha et al, ) and a significant positive correlation between 2AP and GABA in the grains was also observed for the “Yuxiangyouzhan” (Mo et al, ). Additionally, nitrogen fertilization has great impacts on 2AP formation and accumulation (Mo et al, ; Ren et al, ). Therefore, the main reasons that GABA and N regulate the aroma formation are as follows: (a) GABA is directly related to 2AP formation; and (b) the GABA and N regulate the physio‐chemical parameters of 2AP formation.…”
Section: Discussionmentioning
confidence: 99%
“…To increase 2-AP content in fragrant rice grain, many crop management strategies have been introduced, such as fertilizer application, water management, and even light control. Previous studies have shown that extra nitrogen applied at the booting stage could induce increases in 2-AP concentrations in fragrant rice [7]. The study of Bao [8] revealed the molecular basis for increased 2-AP content under drying conditions in fragrant rice.…”
Section: Introductionmentioning
confidence: 99%